Influence of Nostoc muscorum on microbial activity and soil aggregation - PALMA, R M; CAIRE, G ZULPA DE; ZACCARO, M C; CANO, M STORNI DE (The Indian Journal of Agricultural Sciences, 2013)
The effect of sodic soil of exopolysaccharide isolated from Nostoc muscorum or the addition of a cyanobacterial mass proliferation were evaluated in a greenhouse experiment. To establish the effect of biomass and exopolysaccharide on the structure, oxidizable carbon and soluble carbon contents and microbial activity of the soil, two treatments were carried out (inoculations with biomass and exopolysaccharide). N. muscorum mass and exopolysaccharide application to the soil promotes aggregation and aggregate stability along 2 years of treatment. The slow organic C build-up due to these treatments may have resulted from the high microbial activity assessed. The exopolysaccharide application was more effective for macroaggregates (<500um) formation, this soil with low content of organic C, assessing soils inoculated with cyanobacterial mass and exopolysaccharide.